Design of a bidirectional DC/DC converter for a hybrid electric drive system with dual-battery storing energy - Venkata Govardhan Rao, Kambhampati; Kumar, Malligunta Kiran; Goud, B. Srikanth; Bajaj, Mohit; Abou Houran, Mohamad; Kamel, Salah (Frontiers in Energy Research, 2022)
Electric vehicles are projected to play an important role in the present and ensuing transportation as global environmental and energy issues become more serious. Looking into the growing popularity of electric vehicles, we need to pay even more attention to battery energy storage systems. Electric vehicles in the traditional sense rely on a battery to provide electricity. Influential requirements (acceleration and braking) will deteriorate the battery, or it may not be feasible to use it at all in some instances, due to the battery’s compactness. This paper proposes a Bidirectional DC/DC Converter topology and investigates its operation modes. The proposed converter can be used in hybrid electric vehicles. Hybrid electric vehicles use this converter type to connect a primary battery (ES1), an extra battery (ES2), and an adjustable voltage bus. Both step-up (i.e., Dual-source low-voltage powering mode) and step-down (i.e., energy-regenerating high-voltage dc-link mode) modes of operation are possible with the proposed converter, allowing bidirectional power flow. Furthermore, the model can handle the flow of electricity between any two low-voltage sources. For the proposed Bidirectional DC/DC Converter, two ways of power transmission, circuit design, and operation modes are analyzed. A MATLAB-Simulink model of the proposed, and the system is developed based on a Digital Signal Processor flow chart, and the results of the simulation as well as the performance of the system are discussed.